(Un)translatability revisited: transmetic and intertextual puns in Viktor Pelevin’s Generation “P” and its translations - Roman Ivashkiv (The European Journal of Humour Research, 2019)
Babylen Tatarsky, the protagonist in Russian writer Viktor Pelevin's novel Generation “P” (translated into English by Andrew Bromfield as Homo Zapiens), works to adapt American advertisements for the Russian market and witnesses how the reality of Russia’s tumultuous 1990s is replaced by a consumer-driven television simulation. Puns in the advertising slogans that Tatarsky translates, interspersed throughout Generation “P”, are central to its plot. Some of these puns exhibit greater sophistication than others: in addition to utilizing homonymy, homophony, homography, paronymy, and polysemy, they involve transmesis, multilingualism, and intertextuality. This article compares how Pelevin’s translators (English, German, Polish, Spanish, and French) approached these difficult puns. The objective of this comparative analysis is to demonstrate how the intertext(s) evoked through wordplay may, on the one hand, impede translation, but, on the other, open avenues for creative solutions, by producing new traces and echoes of meaning that make the act of translation possible. The issues raised by the various translations point to a need to re-examine the roles and tasks of the translator and underscore the importance of keeping the (un)translatability debate open. Ultimately, this article aims to contribute to the ongoing reconceptualization of what literary translation is and, especially, what it does: with texts, readers, literatures, and, above all, with language.